Las políticas públicas y sus repercusiones en la actividad pesquera de la provincia de Santa Cruz, 1983-2000 - Cepparo, María Eugenia; Gabrielidis, Graciela; Prieto, Estela; Huertas, Marta; Diez, Patricia; Llosa, Macarena; Grosso, Virginia (2006)

(untitled)
Fil: Cepparo, María Eugenia.